Microanalysis of DNA by stripping transfer voltammetry - Jelen, Frantisek; Kourilová, Alena; Pecinka, Petr; Palecek, Emil (Bioelectrochemistry (Amsterdam, Netherlands), 2004)
A cathodic stripping transfer voltammetric procedure for trace determination of DNA and its components is described. The method is based on the DNA acid hydrolysis with subsequent electrochemical determination of released purine bases. In the first step, DNA is hydrolyzed for 30 min in 0.5 M perchloric acid at 75 degrees C. The electrochemical step involves generation of Cu(I)-purine base complex on a mercury electrode surface, transfer of electrode with accumulated complex into supporting electrolyte where voltammetric measurement is performed. Analysis is carried out in 14-microl drop volume (two-electrode connection) or in 30-microl drop (three-electrode connection) on a platinum plate, which is used as a counter electrode. Blank electrolyte contains 0.05 M borate buffer, pH 9.2 with 6.3 microM Cu(II). We could observe voltammetric signal at hydrolyzed nucleosides, nucleotides, ODN, and DNA containing purine bases. We are able to accumulate under the controlled potential and determine subnanomolar concentration of DNA corresponding to the amount of 200 pg of DNA.
Keywords: Purines; Copper; Electrodes; biosenzitivní techniky; puriny; Electrochemistry; Oligodeoxyribonucleotides; reprodukovatelnost výsledků; Reproducibility of Results; mikrochemie; elektrody; Biosensing Techniques; oligodeoxyribonukleotidy; elektrochemie; Microchemistry; Sensitivity and Specificity; senzitivita a specificita; DNA; měď